KESESUAIAN POLA DASAR SISTEM DJATI PRATIWI PADA WANITA DEWASA BERTUBUH IDEAL - Qomariah, Ana; Zahri, Wildati; Yasnidawati, Yasnidawati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
The arm of this research is to reveal 1) the lack of Djati Pratiwi basic pattern system for the lady with ideal body; 2) The way to fix the lack of Djati Pratiwi basic pattern system for lady with iseal body; 3) the suitability of Djati Pratiwi basic pattern system for the lady with ideal body. The kind of this research is applied research. The object of this research is Djati Pratiwi basic pattern that have 4 times fitting on the lady with ideal body, with 5 panelists whichÂ are the expert lecturers that expert in making pattern. Data collection of this research by giving the questionnaire using Likert scale and analyzed by using modus, used to determine the most tendency in suitability appraisal of Djati Pratiwi basic pattern among ladies with ideal body. The result shows that there is the lack of Djati Pratiwi basic system on shoulder length, shoulder line on the shoulder tip, chest, side line, armhole is not, arm center line, top arm height and side line of the skirt on the waist and on the pelvis. the discrepancy was fitted so the Djati Pratiwi basic pattern system can be suitable the ideal body. Â Kata kunci: Kesesuaian pola dasar sistem Djati Pratiwi, Wanita dewasa bertubuh ideal.